Kearifan Lokal Masyarakat dalam Mitigasi Bencana Banjir di Kecamatan Sungai Tabuk: Community Local Wisdom in Flood Disaster Mitigation in Sungai Tabuk Sub-district - Rusmaniah, Rusmaniah; Arisanty, Deasy; Abbas, Ersis Warmansyah; Angriani, Parida (Anterior Jurnal, 2025)
The geographical conditions of the Sungai Tabuk sub-district located in the Martapura river basin and has limited capacity make this area prone to flooding. However, the people in the area still choose to survive by applying local wisdom in dealing with flooding. The purpose of this study is to describe local wisdom in flood disaster mitigation in Sungai Tabuk sub-district. This research was conducted using a qualitative descriptive approach. Data collection techniques used were from observation, interviews, and documentation. Data analysis in this study included stages in data reduction, data presentation, conclusion, and verification. In the validity test, this study used data triangulation, technical triangulation, and time triangulation. From the research that has been conducted, the results of flood disaster mitigation carried out in Sungai Tabuk sub-district include: 1) pre-disaster there is early warning and building flood-resistant houses, 2) disaster response the community makes ampar-ampar, assistance from Karang Taruna, 3) post-disaster the community carries out the tradition of cooperation.